Predicción de la eficiencia de dosis seminales bovinas en inseminación artificial a tiempo fijo - Cerutti, Dante (2019)
Fixed-time artificial insemination (FTAI) technique is a high impact genetic improvement biotechnology applied in beef herds breeded in marginal areas of\nArgentina. For the success of it, one of the factors to take into account is the\nquality of the semen that reaches the places of application of the FTAI\nbiotechnology. Nevertheless, to evaluate the fertilizing capacity of the semen to\nbe used, only laboratories with a basic level of equipment are available. On the other hand, it is important to have predictive evaluation techniques, as accurate as possible, of the field behavior of the seminal doses. Three lots of 108, 94 and 50 British breed beef cows were used, and sperm motility, acrosome integrity,\nosmotic resistance test, endosmosis test, live/dead relationship and percentage of pregnancy of the semen used were compared under two thawing protocols. The\nresult pointed out that the endosmosis test is a valid, low cost, objective and and\nof easy in laboratories with low complexity to evaluate the fertilizing capacity of\nbovine semen in a fixed-time artificial insemination program.